Numerical study of advanced friction modelling for sheet metal forming: Influence of the die local roughness. (January 2022) - Zabala, Alaitz; de Argandoña, Eneko Sáenz; Cañizares, Daniel; Llavori, Iñigo; Otegi, Nagore; Mendiguren, Joseba
Abstract: Numerical simulation of sheet metal forming processes has become indispensable in the last decades. Although the complexity of the frictional behaviour is identified as a key factor for the prediction accuracy, the industry commonly considers a constant friction coefficient for the whole tool. Furthermore, the influence of roughness distribution of the tool in the friction behaviour has not yet been addressed. In this study the influence of the die local roughness in an advanced friction model has been evaluated in three industrial automotive components. The newly implemented advanced friction model (TriboZone) is suggested for advance or mature process verifications. Highlights: An industrial mass study surface topography at multiple tools has been carried out. The radii present the lowest roughness followed by the flat areas. Constant friction model is the most conservative. The model with local roughness leads to higher draw-in. The advance model efficiency is worth it for mature models.